Ag enhanced electrochemical performance for Na2Li2Ti6O14 anode in rechargeable lithium-ion batteries. Issue 6 (1st May 2016) - Qian, Shangshu; Yu, Haoxiang; Yan, Lei; Li, Peng; Lin, Xiaoting; Bai, Ying; Wang, Songjing; Long, Nengbing; Shui, Miao; Shu, Jie
Abstract: Due to the characteristics of an electronic insulator, Na2 Li2 Ti6 O14 always suffers from low electronic conductivity as anode material for lithium storage. Via Ag coating, Na2 Li2 Ti6 O14 @Ag is fabricated, which has higher electronic conductivity than bare Na2 Li2 Ti6 O14 . Enhancing the Ag coating content from 0.0 to 10.0 wt%, the surface of Na2 Li2 Ti6 O14 is gradually deposited by Ag nanoparticles. At 6.0 wt%, a continuous Ag conductive layer is formed on Na2 Li2 Ti6 O14 . While, particle growth and aggregation take place when the Ag coating content reaches 10.0 wt%. As a result, Na2 Li2 Ti6 O14 @6.0 wt% Ag displays better cycle and rate properties than other samples. It can deliver a lithium storage capacity of 131.4 mAh g −1 at 100 mA g −1, 124.9 mAh g −1 at 150 mA g −1, 119.1 mAh g −1 at 200 mA g −1, 115.8 mAh g −1 at 250 mA g −1, 111.9 mAh g −1 at 300 mA g −1 and 109.4 mAh g −1 at 350 mA g −1, respectively.